Influence of Playing Genshin Impact on the Lifestyle and Social Skills of the Students at Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Genshin Impact is an online game in the massively multiplayer online role-playing game(MMORPG) genre, which is played by organic or noncomputer/AI players simultaneously. Theresearcher aims to establish and evaluate if there is the influence of playing Genshin Impacton Sleep habits, Eating tendencies, and Physical Activities in a healthy lifestyle and IntimateRelationships (Family, Friends, and partners), Acquaintances (Workmates, Classmates), andGeneral public (random people, virtual groups) in the area of social skills of the respondents.Influence of playing Genshin Impact has been proven by the researchers that even thoughGenshin is a new game, it certainly has an influence on students in Bestlink College of thePhilippines but nevertheless, it is still not too crucial or alarming to the point that it makes themaddicted to the game and affects their lifestyle and social, behavioral skills.Even though they play Genshin impact, they still do not fully forget their responsibilities athome, school, work, friends, and themselves. Genshin Impact can't be easily removed fromthe students' routine. Therefore, the researchers will establish a guide in order to at leastminimize the risk of getting too much in the game while balancing their healthy lifestyle andsocial life.
Keywords: Psychology